2021
DOI: 10.1021/acs.jpcc.1c04676
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Defects on the Interfacial Thermal Conductance between n-Heneicosane in Solid and Liquid Phases and a Graphene Monolayer

Abstract: The molecular level mechanism of heat transport across the interface between solid and liquid n-heneicosane and monolayer graphene with three types of defects (single-vacancy, multivacancy (MV), and Stone–Wales (SW) (SW1 and SW2 cases are considered based on the orientation of the defects) has been studied using nonequilibrium molecular dynamics simulations. The influence of the alignment of an ideal crystal structure (heneicosane molecules positioned perpendicular and parallel to the graphene basal plane) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…While SDHF IS has been studied extensively, ,,,,, the dependence of SDHF IL on ε SL is systematically studied for the first time here. By computing SDHF IS and SDHF IL for all values of ε SL and contrasting these with VDOS IS and VDOS IL , respectively, we are also able to identify why the VDOS Overlap fails to explain the crossover.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While SDHF IS has been studied extensively, ,,,,, the dependence of SDHF IL on ε SL is systematically studied for the first time here. By computing SDHF IS and SDHF IL for all values of ε SL and contrasting these with VDOS IS and VDOS IL , respectively, we are also able to identify why the VDOS Overlap fails to explain the crossover.…”
Section: Resultsmentioning
confidence: 99%
“…Alosious et al 63 illustrated that the rise in G due to the reduction in confinement at a carbon-nanotube/water interface is associated with an increase in the similarity of vibrations between the solid and liquid. Zhou et al 64 showed that the enhancement in G due to the presence of atomic defects at graphene/hydrocarbon interfaces is linked to an increase in the coupling of in-plane vibrations between the interfacial solid and liquid. Importantly, Sääskilahti et al 65 demonstrated that the rise in G resulting from an increase in artificially tuned wettability at an LJ solid/liquid interface is associated with an enhancement in the coupling of high-frequency vibrations from the solid to the liquid, as well as an improvement in the coupling of in-plane vibrations.…”
Section: Introductionmentioning
confidence: 99%